2013
DOI: 10.1262/jrd.2012-163
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Potential of Oocytes is Impaired in Cattle with Liver Abnormalities

Abstract: Here, we investigated the effect of liver abnormality on the developmental potential of bovine oocytes. Good quality oocytes from healthy cows and from animals with a liver abnormality were matured and fertilized in vitro and then cultured to the blastocyst stage. On day 7 after fertilization, embryo cleavage and development were assessed. The concentrations of glucose, nonesterified fatty acid (NEFA), γ-glutamyl transpeptidase (γ-GTP), β-hydroxybutyrate (BHBA) and glutathione were measured in follicular fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Thus, the present study indicates that the high GGT activity observed in anovulatory cows may not have been caused by fatty liver. However, liver disorders, including hepatitis, degeneration, and telangiectasia, are all more common in cows with fatty livers [ 43 ]. Therefore, anovulatory cows with higher GGT activity may be more likely to acquire such disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the present study indicates that the high GGT activity observed in anovulatory cows may not have been caused by fatty liver. However, liver disorders, including hepatitis, degeneration, and telangiectasia, are all more common in cows with fatty livers [ 43 ]. Therefore, anovulatory cows with higher GGT activity may be more likely to acquire such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ovulation by 3 weeks postpartum was associated with high fertility, supporting the results of previous work [ 2 , 3 , 4 ]. Moreover, cows with liver disorders exhibited higher GGT activity in follicular fluid, as well as a negative correlation between the GGT activity of the follicular fluid and the rate of blastocyst formation after in vitro fertilization [ 43 ]. Sarentonglaga et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all ATP is generated in the mitochondria in oocytes [ 29 ], and ATP content in oocytes is higher during the MII stage than the GV stage, indicating that high ATP content is a prerequisite for successful oocyte maturation [ 10 , 18 , 30 ]. In the present study, we compared mitochondrial function by measuring ATP content and membrane potential between the two liver conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between the negative energy condition and infertility has been reported previously [ 2 , 6 ], few studies have examined the relationship between liver damage and the low quality of bovine oocytes [ 7 , 8 , 9 , 10 ]. In these studies, one of the prominent features of oocytes derived from cows with liver damage was the high frequency of abnormal fertilization [ 8 ]; however, the molecular mechanism underlying fertilization abnormalities are unclear.…”
mentioning
confidence: 99%